44.2k views
3 votes
How do I solve 2m + n = 2 and 3m - 2n = 3 using substitution?

User Yifei
by
4.9k points

1 Answer

5 votes


\huge \boxed{\mathbb{QUESTION} \downarrow}

  • Solve 2m + n = 2 and 3m - 2n = 3 using substitution.


\large \boxed{\mathfrak{Answer \: with \: Explanation} \downarrow}

We can use the substitution method to solve linear equations of this form. Let's solve for m & n.


\left. \begin{array} { l } { 2 m + n = 2 } \\ { 3 m - 2 n = 3 } \end{array} \right.

To solve a pair of equations using substitution, first solve one of the equations for one of the variables. Then substitute the result for that variable in the other equation.


2m+n=2, \: 3m-2n=3

Choose one of the equations and solve it for m by isolating m on the left-hand side of the equal sign.


2m+n=2

Subtract n from both sides of the equation.


2m=-n+2

Divide both sides by 2.


m=(1)/(2)\left(-n+2\right) \\

Multiply 1/2 times -n+2.


m=-(1)/(2)n+1 \\

Substitute
-(n)/(2)+1\\ for m in the other equation, 3m-2n=3.


3\left(-(1)/(2)n+1\right)-2n=3 \\

Multiply 3 times
-(n)/(2)+1\\.


-(3)/(2)n+3-2n=3 \\

Add
-(3n)/(2)\\ to -2n.


-(7)/(2)n+3=3 \\

Subtract 3 from both sides of the equation.


-(7)/(2)n=0 \\

Divide both sides of the equation by
-(7)/(2)\\, which is the same as multiplying both sides by the reciprocal of the fraction.


\large \underline{\underline{ \bf \: n=0 }}

Substitute 0 for n in
m=-(1)/(2)n+1\\. Because the resulting equation contains only one variable, you can solve for m directly.


\large \underline{ \underline{\bf \: m=1 }}

The system is now solved.


\huge \boxed{ \boxed{ \bf \: m=1, \: n=0 }}

User Touts
by
5.3k points